A new crotamine-like from the rattlesnake (Crotalus durissus cumanensis) venom causing damages: Qualitative and Quantitative Cytotoxic Studies on subcellular and neuromuscular structures - García, Estefanie; Finol†, Hector José; González, Roschman; Rodríguez-Acosta, Alexis (Revista Científica de la Facultad de Ciencias Veterinarias, 2022)
A quantitative model to expose the adrenal gland sub-cellular alterations produced by crotamine-like (C-L) from rattlesnake venom during 3, 6 and 24 hours (h), and also qualitative changes on mice neuromuscular structures in vivo were observed and calculated by transmission electron microscopy. A pure crotamine-like (C-L) isoform was obtained using a cationic exchange chromatography column from the rattlesnake Crotalus durissus cumanensis venom. The C-L SDS-PAGE (15.5 %) under non-reduced conditions exhibited a molecular mass of ~3 kDa single band. The C-L in vivo qualitative experiments induced ultrastructural changes in mouse neuromuscular structures at 3, 6 and 24 h, such as reduction in the number of acetylcholine vesicles, disorganisation of the secondary synaptic clefts, enlargement of the sub-sarcolemma space and alteration of the mitochondria morphology, number and cristae. Regarding neurotoxic actions in vivo, the animals injected with C-L presented spastic paralysis of the hind limbs. The quantitative alterations studied on the capillaries, the nucleus, the mitochondria the lipid inclusions, and the smooth endoplasmic reticulum were observed from 3 to 24 h after C-L injection. As far as it is known from the literature review, there are no quantitative records of similar sub-cellular alterations caused by crotamine.